The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/jf001003y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Replacement of Gum Arabic with Carbohydrates on Its Microencapsulation Properties

Abstract: Gum arabic solutions (10% w/v) were emulsified with soy oil at oil/gum ratios of 0.25-5.0. At oil/gum ratios <1.0, it was established that gum arabic could be partially replaced with a nonsurfactant carbohydrate. To assess different carbohydrates as replacers for gum arabic, emulsions and spray-dried emulsions of soy oil and mixed solutions (10% w/v) of gum arabic and a range of carbohydrate wall materials (oil/gum = 0.5) were prepared and analyzed. Maize starch and glucose were ineffective as partial replacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 6 publications
5
53
0
1
Order By: Relevance
“…The MEE is related to the powder particle size and is measured as the degree of oil extracted from the capsules. 10, 13 Kim and Morr 10 showed that GA had a poorer retention of orange oil than whey proteins. In general, the values obtained in this work were lower than those reported for complex microencapsulation of CLA in CLA-α-CD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MEE is related to the powder particle size and is measured as the degree of oil extracted from the capsules. 10, 13 Kim and Morr 10 showed that GA had a poorer retention of orange oil than whey proteins. In general, the values obtained in this work were lower than those reported for complex microencapsulation of CLA in CLA-α-CD.…”
Section: Resultsmentioning
confidence: 99%
“…9 -12 Gum arabic (GA) has excellent emulsification properties and it is widely used for the retention and protection of oils. However, GA is an expensive ingredient and its availability and cost are subject to fluctuations, 13 hence there is a need to evaluate alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has therefore been applied in the microencapsulation of many volatile substances (ROSENBERG; KOPELMAN; TALMON,1990;BHANDARI et al, 1992;BUFFO;REINECCIUS, 2000;LIU et al, 2001;McNAMEE;O'RIORDAN;O'SULLIVAN, 2001;FINNEY;BUFFO;REINECCIUS, 2002;SOOTTITANTAWAT et al, 2003, TURCHIULI et al, 2006BARANAUSKIENÉ et al, 2006) in addition to many other ingredients described in a recent up-dated literature survey on the subject by Gharsallaoui et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…0.02À1000 Baranauskiené et al, 2006Baranauskiené et al, , 2007Bhandari et al, 1992;BringasLantigua et al, 2011;Chen et al, 2013;Choi et al, 2009;Finney et al, 2002;Jimenez et al, 2010;Fabra et al, 2012;Kaasgaard and Keller, 2010;Kim and Morr, 1996;Ko et al, 2012;Li et al, 2013;McNamee et al, 1998McNamee et al, , 2001Paramita et al, 2012;Penbunditkul et al, 2012;Shah et al, 2012;Sillick and Gregson, 2012;Soottitantawat et al, 2005Soottitantawat et al, , 2007Sosa et al, 2013;Syamaladevi et al, 2012;Yang et al, 2012a,b;Yeo et al, 2005;Zandi et al, 2014.…”
mentioning
confidence: 99%